Religiosity and Misanthropy across the Racial and Ethnic Divide - Valente, Rubia R. (Religions, 2023)
The systematic study of misanthropy, the lack of trust in humanity, has proliferated over the last 30 years. One prominent line of research details racial and ethnic disparities in levels of misanthropy, but pays little attention to the role of religiosity, while another focuses attention on religiosity and its impact on levels of misanthropy, with only scant attention to the role of race and ethnicity. Little attempt has been made to synthesize these two strands of literature to address an important unanswered question: Does the association between religiosity and misanthropy vary by racial and ethnic group? To answer this question, we pooled data from the General Social Survey (GSS, 2000–2018). Among other things, we find stark racial differences between Blacks and Whites in terms of the effect of religiosity on misanthropy. Blacks and Latinos who attend religious services weekly (social religiosity) have significantly higher levels of misanthropy than others, while Whites who attend weekly services are less likely to be misanthropic. An important takeaway is that service attendance (a type of social capital) is associated with feelings of misanthropy for all groups (albeit in opposite directions for Blacks and Latinos versus Whites), rather than personal acts of prayer (individual religiosity). When it comes to misanthropy, we conclude that religion works differently for minorities compared with Whites. We discuss the implications of our findings for future research.